The perceived value of using BIM for energy simulation - Lewis, Anderson M., author; Valdes-Vasquez, Rodolfo, advisor; Clevenger, Caroline, committee member; Atadero, Rebecca, committee member (Colorado State University. Libraries, 2014)
Building Information Modeling (BIM) is becoming an increasingly important tool in the Architectural, Engineering & Construction (AEC) industries. Some of the benefits associated with BIM include but are not limited to cost and time savings through greater trade and design coordination, and more accurate estimating take-offs. BIM is a virtual 3D, parametric design software that allows users to store information of a model within and can be used as a communication platform between project stakeholders. Likewise, energy simulation is an integral tool for predicting and optimizing a building's performance during design. Creating energy models and running energy simulations can be a time consuming activity due to the large number of parameters and assumptions that must be addressed to achieve reasonably accurate results. However, leveraging information imbedded within Building Information Models (BIMs) has the potential to increase accuracy and reduce the amount of time required to run energy simulations and can facilitate continuous energy simulations throughout the design process, thus optimizing building performance. Although some literature exists on how design stakeholders perceive the benefits associated with leveraging BIM for energy simulation, little is known about how perceptions associated with leveraging BIM for energy simulation differ between various green design stakeholder user groups. Through an e-survey instrument, this study seeks to determine how perceptions of using BIMs to inform energy simulation differ among distinct design stakeholder groups, which include BIM-only users, energy simulation-only users and BIM and energy simulation users. Additionally, this study seeks to determine what design stakeholders perceive as the main barriers and benefits of implementing BIM-based energy simulation. Results from this study suggest that little to no correlation exists between green design stakeholders' perceptions of the value associated with using information from BIMs to inform energy simulation and their engagement level with BIM and/or energy simulation. However, green design stakeholder perceptions of the value associated with using information from BIMs to inform energy simulation and their engagement with BIM and/or energy simulation may differ between different user groups (i.e. BIM users only, energy simulation users only, and BIM and energy simulation users). For example, the BIM-only user groups appeared to have a strong positive correlation between the perceptions of the value associated with using information from BIMs to inform energy simulation and their engagement with BIM. Additionally, this study suggests that the top perceived benefits of using BIMs to inform energy simulations among green design stakeholders are: facilitation of communication, reducing of process related costs, and giving users the ability examine more design options. The main perceived barrier of using BIMs to inform energy simulations among green design stakeholders was a lack of BIM standards for model integration with multidisciplinary teams. Results from this study will help readers understand how to better implement BIM-based energy simulation while mitigating barriers and optimizing benefits. Additionally, examining discrepancies between user groups can lead the identification and improvement of shortfalls in current BIM-based energy simulation processes. Understanding how perceptions and engagement levels differ among different software user groups will help in developing a strategies for implementing BIM-based energy simulation that are tailored to each specific user group.
Keywords: analysis; perceptions; energy simulation; energy modeling; BIM